Financial Management and Performance of Banks in Kabale District A Case Study of Stanbic Bank Kabale. - Alinda, Joanita (Kabale University, 2023)
Financial management comprises the processes, systems, internal controls, and practices relating to the way the institutions manage revenues, expenses, assets, liabilities, and contingencies. This also involves managing risks and monitoring the financial performance; including budgeting and reporting on these functions both internally and externally (Queens Land Financial Practice. The financial management culture of an organization starts with the actions of the executive director, but it is fully realized in the design of the business process that the organization adopts. The purpose of the study was to assess the financial management and performance of banks in Kabale district a case study of Stanbic Bank Kabale.